The role of vagus nerve stimulation in refractory epilepsy - Tatiana Von Hertwig Fernandes de Oliveira; Alexandre Novicki Francisco; Zeferino Demartini Junior; Sergio Leandro Stebel (Arquivos de Neuro-Psiquiatria)
ABSTRACT Vagus nerve stimulation is an adjunctive therapy used to treat patients with refractory epilepsy who are not candidates for resective surgery or had poor results after surgical procedures. Its mechanism of action is not yet fully comprehended but it possibly involves modulation of the locus coeruleus, thalamus and limbic circuit through noradrenergic and serotonergic projections. There is sufficient evidence to support its use in patients with focal epilepsy and other seizure types. However, it should be recognized that improvement is not immediate and increases over time. The majority of adverse events is stimulation-related, temporary and decreases after adjustment of settings. Future perspectives to improve efficacy and reduce side effects, such as different approaches to increase battery life, transcutaneous stimulation and identification of prognostic factors, should be further investigated.